Corrosion evaluation of Ti-6Al-4V parts produced with electron beam melting machine. Issue 2 (21st March 2016) - Abdeen, Dana H.; Palmer, Bruce R.
Abstract : Purpose: This paper aims to evaluate the corrosion behavior of Ti-6Al-4V parts produced with electron beam melting (EBM) machine and compare it with wrought Ti-6Al-4V alloy. Design/methodology/approach: Potentiodynamic and potentiostatic tests were applied on EBM Ti-6Al-4V in 3.5 per cent mass NaCl solution to determine the pitting potential and critical pitting temperature (CPT). A relation between pitting potential and temperature was established for EBM Ti-6Al-4V alloy by conducting potentiodynamic testing under different temperatures. CPT was also measured for EBM Ti-6Al-4V alloy in 3.5 per cent mass NaCl solution at a standard potential of 800 mV vs saturated calomel electrode (SCE). The same tests were performed on wrought Ti-6Al-4V for comparison purposes. Moreover, CPT for EBM Ti-6Al-4V alloy was measured in 3.5 per cent mass NaCl solution of different pH of 2.0, 5.7 and 10.0 to examine the effect of aggressive conditions on the pitting corrosion of EBM alloy. Findings: Potentiodynamic test resulted in a relatively high pitting potential of EBM alloy, which was close to the pitting potential of wrought alloy even at higher temperatures. In addition, EBM samples did not pit when potentiostatic test was performed at 800 mV vs SCE, even at high and low values of pH. Originality/value: EBM Ti-6Al-4V alloy has been increasingly playing an important role in aerospace, automobile and industrial fields. The technique and conditions of manufacturing form voids and increase roughness of the exterior surface of EBM objects, which might increase the tendency to initiate pitting corrosion within its holes and surface folds. This article shows that, despite surface variations and porosity in EBM Ti-6Al-4V alloy, the material maintained its corrosion resistance. It was found that the corrosion behavior of EBM alloy was close to that of the conventionally made wrought Ti-6Al-4V alloy.